Civil justice reconsidered : toward a less costly, more accessible litigation system - Croley, Steven P., 1965- (New York University Press, 2017)
"In Civil Justice Reconsidered, Steven Croley demonstrates that civil litigation is, for the most part, socially beneficial. An effective civil litigation system is accessible to parties who have suffered legal wrongs, and it is reliable in the sense that those with stronger claims tend to prevail over those with weaker claims. However, while most of the system's failures are overstated, they are not wholly off base; civil litigation often imposes excessive costs that, among other unfortunate consequences, impede access to the courts, and Croley offers ways to reform civil litigation in the interest of justice for potential plaintiffs and defendants, and for the rule of law itself"--Publisher's web site, viewed February 10, 2017